2022
DOI: 10.1177/03611981221112096
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Airline Passengers during Covid-19 Outbreak to Improve Service Quality: Topic Modeling Approach to Complaints with Latent Dirichlet Allocation Algorithm

Abstract: The COVID-19 pandemic has deeply affected the airline industry, as it has many sectors, and has created tremendous financial pressure on companies. Flight bans, new regulations, and restrictions increase consumer complaints and are emerging as a big problem for airline companies. Understanding the main reasons triggering complaints and eliminating service failures in the airline industry will be a vital strategic priority for businesses, while reviewing the dimensions of service quality during the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…As adapted from Blei, Ng, and Jordan [23], Figure 2 illustrates the graphical representation of LDA. Additionally, LDA has been effectively utilized in numerous studies across a variety of fields, including business, technology, and society, to analyze textual data [25][26][27][28][29][30].…”
Section: Methodsmentioning
confidence: 99%
“…As adapted from Blei, Ng, and Jordan [23], Figure 2 illustrates the graphical representation of LDA. Additionally, LDA has been effectively utilized in numerous studies across a variety of fields, including business, technology, and society, to analyze textual data [25][26][27][28][29][30].…”
Section: Methodsmentioning
confidence: 99%
“…Çallı used Latent Dirichlet Allocation to analyze 10,594 airline complaints d ing the COVID-19 pandemic. Their study revealed primary triggers for customer co plaints and proposed a decision support system for identifying significant service failur [26] In this study, we performed model-based feature selection, as in a study by Mudam and Schuff [11], but we supplemented it with LDA-based topic modeling to exam whether the features fully reflect the entire text.…”
Section: Methodsmentioning
confidence: 99%
“…LDA has been used extensively for topic modelling [25][26][27][28][29]. For example, Çalli and Çalli [30] applied LDA to a dataset containing 10,594 airline-customers complaints from two Turkish airlines during the COVID-19 pandemic. Their study generated seven topics as the latent topics that customers complaints were about and used a qualitative human interpretation approach to validate the topics.…”
Section: Related Workmentioning
confidence: 99%